Analysis of good tourism governance dynamics in Kampung Lali Gadget tourism village - Aliefa Rizkya Ananda; Rosyidatuzzahro Anisykurlillah (Satwika : Kajian Ilmu Budaya dan Perubahan Sosial, 2025)
Kampung Lali Gadget (KLG), an educational tourism village in Pagerngumbuk Village, Sidoarjo Regency, promotes traditional cultural values to reduce reliance on gadgets. Despite its unique conceptual positioning, the management of this tourism destination continues to face challenges, including uneven community participation, limited multi-stakeholder partnerships, and an evaluation system that is not yet fully measurable. Previous studies have rarely examined the application of Good Tourism Governance in educational tourism villages; therefore, this study aims to analyze disparities in implementing the ten Good Tourism Governance principles outlined by Sunaryo (2013) in KLG. This research employs a descriptive qualitative approach through in-depth interviews, observations, and document reviews with informants from the management team, local community, village government, private sector, and visitors. The findings reveal that governance implementation includes participation in a single hamlet, asset-based local economic partnerships, environmental conservation integrated into educational programs, digital promotion dominated by tourism managers, and internal–external evaluations lacking inclusivity. The complexity of local socio-cultural dynamics influences patterns of collaboration and benefit distribution. Theoretically, this study expands the understanding of adapting community-based tourism governance to local characteristics while providing guidance on measurable tourism governance for similar destinations.   Kampung Lali Gadget (KLG) sebagai desa wisata edukasi di Desa Pagerngumbuk Kabupaten Sidoarjo yang mempromosikan konsep budaya tradisional untuk mengurangi ketergantungan pada gadget. Meskipun menjadi destinasi yang berkonsep unik, pengelolaan wisata ini masih menghadapi tantangan seperti partisipasi masyarakat yang tidak merata, kemitraan multi-pihak yang terbatas, dan sistem evaluasi yang belum sepenuhnya terukur. Studi sebelumnya jarang mengkaji penerapan Good Tourism Governance di desa wisata edukasi, sehingga penelitian ini bertujuan menganalisis ketiimpangan dalam penerapan sepuluh prinsip Good Tourism Governance menurut Sunaryo (2013) di Kampung Lali Gadget. Penelitian ini menggunakan metode kualitatif deskriptif melalui wawancara mendalam, observasi, dan tinjauan dokumentasi dengan informan dari pihak pengelola, masyarakat, pemerintah desa, sektor swasta, dan pengunjung. Hasil penelitian menunjukkan bahwa implementasi prinsip-prinsip tata kelola meliputi partisipasi terpusat di satu dusun, kemitraan ekonomi berdasarkan aset lokal, konservasi lingkungan yang terintegrasi ke dalam program pendidikan, promosi digital yang berpusat pada pengelola wisata, dan evaluasi internal dan eksternal yang belum inklusif. Kompleksitas dinamika sosial-budaya lokal mempengaruhi pola kolaborasi dan distribusi manfaat. Secara teoritis, penelitian ini memperluas pemahaman tentang adaptasi tata kelola pariwisata berbasis komunitas terhadap karakteristik lokal, sementara secara praktis memberikan panduan tentang tata kelola wisata yang dapat diukur untuk destinasi serupa.